Data Logger Panel Surya Berbasis Mikrokontroler Arduino Nano - Rustam Efendi; Arjal Tando; Supardi Supardi (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2026)
Data loggers play a crucial role in real-time data acquisition and monitoring across various engineering applications, particularly in renewable energy systems such as photovoltaic (PV) panels. However, existing monitoring systems are often limited by relatively high implementation costs and low flexibility in system development and integration. Therefore, this study aims to develop an Arduino-based data logger that is cost-effective, flexible, and capable of real-time monitoring with high temporal resolution for PV systems. The method employed in this research is a design-and-build approach, which includes hardware design, software development, sensor calibration, and direct implementation on a photovoltaic panel system. The developed system is capable of acquiring data with a one-second sampling interval, enabling enhanced monitoring of the dynamic behavior of PV panels. The parameters measured include the output voltage of the panel and the back surface temperature of the photovoltaic panel. The recorded data are automatically stored on an SD card, supporting long-term data storage and further analysis using software such as Microsoft Excel. The experimental results indicate that the system operates reliably and stably under real operating conditions. The measured voltage ranges from 18 to 20 Volts, while the back surface temperature of the photovoltaic panel varies between 28°C and 51°C.